Government Transfers, Work and Wellbeing: Evidence from the Russian Old-Age Pension - Louise Grogan; Fraser Summerfield (Institute of Labor Economics (IZA), 2018)
This paper examines the impacts of a large and anticipated government transfer, the Russian old-age pension, on labor supply, home production and subjective wellbeing. The discontinuity in eligibility at pension age is exploited for inference. The 2006-2011 Russian Longitudinal Monitoring Survey is employed. Causal impacts differ across the sexes. Women reduce market work and appear to increase home production. They report increased wellbeing. Men reduce labor supply without any apparent increase in wellbeing. Pension receipt does not impact household composition.
Keywords: I31; J22; J26; Z13; 330; fuzzy regression discontinuity; subjective wellbeing; pensions; labor supply